An approximation of stockout probabilities in inventory routing problem - Saraçoğlu, Ş. Şükrü. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1985., 1985)
One of the most important variant of the well-known Vehicle Routing Problem is Inventory Routing Problem. We are concerned with the stothastic aspects of this problem. Though a closed form for the stock9ut probability expression is not available for even simplest form of demand distributians, problem is tried to be solved by using a simplified approximated expression. We test the validity and reliability of the expression with simulation methods, then we deal with.the causes of the error resulting from the approximation. Finally by regression methods we estimate a multiplier which minimizes our error.
Keywords: Operations research.